Extinction Risks and the Conservation of Madagascar's Reptiles - Jenkins, Richard K. B. (Public Library of Science, 2014)
BACKGROUND: An understanding of the conservation status of Madagascar's endemic reptile species is needed to underpin conservation planning and priority setting in this global biodiversity hotspot, and to complement existing information on the island's mammals, birds and amphibians. We report here on the first systematic assessment of the extinction risk of endemic and native non-marine Malagasy snakes, lizards, turtles and tortoises. METHODOLOGY/PRINCIPAL FINDINGS: Species range maps from The IUCN Red List of Threatened Species were analysed to determine patterns in the distribution of threatened reptile species. These data, in addition to information on threats, were used to identify priority areas and actions for conservation. Thirty-nine percent of the data-sufficient Malagasy reptiles in our analyses are threatened with extinction. Areas in the north, west and south-east were identified as having more threatened species than expected and are therefore conservation priorities. Habitat degradation caused by wood harvesting and non-timber crops was the most pervasive threat. The direct removal of reptiles for international trade and human consumption threatened relatively few species, but were the primary threats for tortoises. Nine threatened reptile species are endemic to recently created protected areas. CONCLUSIONS/SIGNIFICANCE: With a few alarming exceptions, the threatened endemic reptiles of Madagascar occur within the national network of protected areas, including some taxa that are only found in new protected areas. Threats to these species, however, operate inside and outside protected area boundaries. This analysis has identified priority sites for reptile conservation and completes the conservation assessment of terrestrial vertebrates in Madagascar which will facilitate conservation planning, monitoring and wise-decision making. In sharp contrast with the amphibians, there is significant reptile diversity and regional endemism in the southern and western regions of Madagascar and this study highlights the importance of these arid regions to conserving the island's biodiversity.